(untitled) (Almanack, 2021)
This article explores the advance of the prison reform in the Russian Empire. It examines the governmental department that was the driver of this reform, the Main Prison Administration, and focuses on its policy in the domain of the forced labour of prisoners. Two types of forced labour are of particular interest here. One is the traditional hard penal labour, or katorga, and the other is the obligatory labour for the prisoners serving shorter terms. I outline here how this second type of labour came to play the decisive role in the discourse on punishment in the late imperial period, what kind of conceptions supported it, and how it was implemented throughout the empire.